HUBUNGAN ANTARA DISIPLIN KERJA DENGAN KUALITAS PELAYANAN CONCIERGE PADA HOTEL SAHID JAYA SOLO - M.P, P. Bonusia Agung (JURNAL TALENTA PSIKOLOGI, 2013)
Work discipline is very important to increase success in achieving corporate goal. In addition through the clearly order or regulation, there also be a clearly description of duty and authority in a work discipline. Therefore it be can easily understood by the employee. The population of this study is more than 200 consumers of Hotel Sahid Jaya Solo. This study was taken 100 consumers who are visiting as sample. Product Moment is used to analysis data. The calculation results of the product moment analysis toward the correlation between work discipline and service quality of concierge staff shows that Rxy is 0.75 or 75%. Meanwhile Rxy on the service quality is 0.75 or 75%. Its mean that the estimation model of the variable from the service quality can explain variable of work discipline 75%, while the remain can be explained on the other variables 25%. The conclusion of this study is there is a positive and significant effect of work discipline toward concierge service quality staff. The higher of work discipline will be followed by the higher of service quality in concierge staff. In the contrary the lower of work discipline will be also followed by the lower of service quality in concierge staff.